Oral and maxillofacial lesions in children and adolescents - Renata Lais Xavier Santos; Edmilson Zacarias da Silva Júnior; Maria Carlla Aroucha Lyra; Richard Alonso Ribeiro de Andrade; Mônica Vilela Heimer; Emanuel Sávio de Souza Andrade (Editorial Ciencias Médicas, 2018)
Introduction: Despite the vast literature reporting the prevalence of oral and maxillofacial diseases in the last decades, few studies have focused on lesions biopsied in the pediatric population. Objective: To determine the prevalence of oral and maxillofacial lesions that were biopsied in children and adolescents aged 0-19 years. Methods: Observational and descriptive study. We carried out a retrospective review of 862 reports of pathological examinations performed in an oral pathology laboratory of the northeast of Brazil, during the period from March 2001 to December 2009. The categories were neoplasms, hyperplastic/reactionary lesions, salivary gland lesions, bone lesions, healthy tissues and teeth, oral mucosal lesions, cystic lesions, odontogenic tumors, periapical inflammation, dental alteration and conclusive diagnosis. Results: The epidemiological profile of patients was characterized by females (53.24 %), Caucasian (45.12 %), with a mean age of 13.06 years. Salivary gland lesions were the category with the largest number of cases (182), and mucocele was the most prevalent histopathological diagnosis (18.44 %), with an average size of 1.97 cm. Most cases were asymptomatic (70.88 %). Conclusions: This study showed a predominance of lesions diagnosed as benign, the most prevalent lesions were associated with the salivary gland. Females were the most affected.